The Uniate Church of Belarus in the confrontation between East and West - Morozowa, Svetlana (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the role of the Uniate Church in the Belarusian lands in the context of the rivalry between Eastern and Western Christianity. The author addresses the problem of Belarus’s position between the influences of Byzantium and Rome, as well as Moscow and Poland. The aim of the study is to present the Union of Brest as an attempt to develop an independent model of religious and cultural development. A historical method based on the analysis of religious, polemical, and journalistic sources from the sixteenth and seventeenth centuries is employed. The research demonstrates that the Union was a response to the crisis of Orthodoxy and the growing strength of the Catholic Counter-Reformation. According to the author, it was not merely the result of political pressure but also an attempt to preserve cultural distinctiveness while opening up to the West. At the same time, it encountered strong resistance from parts of society attached to the Orthodox tradition. The analysis indicates that the Uniate Church was an important factor in shaping Belarusian identity and a sphere in which political and religious influences clashed. The Union of Brest was an attempt to reconcile East and West; however, rather than ending religious conflicts, it created new divisions that continued to influence the development of Belarusian society for a long time.